O ensino da matemática para estudantes com Transtorno do Espectro Autista (TEA) - LEMOS, Jordan Marques (2024)
The study focuses on the theme of Inclusive Education and aims to analyze the teaching and learning of Mathematics for students with autism spectrum disorder - ASD. For this, it addresses the concepts of inclusive education, TEA, characteristics of the autistic student and also the mathematical approach for these students, focusing on dyscalculia. The qualitative research carried out is of the literature review type. It was possible to verify, according to the relevant literature, that there is a great difficulty for teachers and others involved in schools to teach Mathematics to this part of the population. Faced with alternative didactics, methodologies that consider the limits and difficulties of these students and with the use of games, it becomes possible for students with ASD to understand Mathematics and assimilate the content in an adequate way, being able to take it into life.